PERSONALITY FORMATION OF FAITH IN THE QURAN - Erwin Pinayungan Dasopang; Putri Ani Dalimunthe; Masrawati Pahutar; Syahrul Wirda (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2022)
The purpose of this research is to explore the process of forming a faithful personality in the heart of a Muslim according to the Qur'an by exploring the meaning of the interpretations of the Qur'an. This research uses a descriptive method with a qualitative approach. The research results show that a believer can be lucky if he occupies the six characteristics. First, a believer is one who prays solemnly by humbling himself before Allah. Second, a believer is one who stays away from useless deeds such as words, deeds, and so on. Third, the believer is one who pays pay zakat by fulfilling it. Fourth, a believer is one who keeps his private parts (sexuality) from the haram except with his wife or slave (concubine), which is not a problem (in the era when there were slaves), if he seeks sexual satisfaction other than with his wife and slaves, such as masturbation, then he has gone beyond the limit by committing an unlawful act. The fifth believer is one who keeps his word and is responsible both individually and collectively for relationships with fellow human beings such as mu'amalah. Sixth, a believer is one who always keeps the five daily prayers.